QIRA’AT SYĀZZAH PRESPEKTIF IBN KHALĀWAIH: KRITIK ATAS QIRA’AT SAB’AH IBN MUJĀHID - Miftahul Janah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This paper aims to examine the qira’at syāzin the view of Ibn Khalawaih. He was a student of Ibn Mujāhid, the originator of the qira’at sab’ah. Nevertheless, despite having the status of teacher and student, they have different judgments about the qira’at syāz. So the qira’at which is considered ṣaḥīḥ by Ibn Mujāhid is sometimes considered syāzby Ibn Khalāwaih. This also shows the different qira’at evaluation standards between the two. This study finally shows contiu and cange in the study of Islamic thought in general and the qira’at region in particular. With a historical and philosophical approach, this study concludes that the difference in the assessment of qira’at between Ibn Mujāhid and Ibn Khalāwaih can be grouped into two; absolute difference and non-absolute difference as an affirmation of Ibn Mujāhid’s previous judgment. The standard assessment of qira’at for both still refers to the same three things, namely; sanad ṣaḥīḥ, according to rasm usmani and according to language rules. The difference lies in the strictness of Ibn Khalawaih in the aspects of sanad, so that the assessment between Ibn Mujāhid and Ibn Khalāwaih is different.